THE ROLE OF MUSIC IN POLITICAL CAMPAIGNSIN INDONESIA - Karya Guna , Bucky Wibawa; Sjoraida , Diah Fatma; Nugraha, Aat Ruchiat (KRIEZ ACADEMY : Journal of development and community service, 2024)
The role of music in political campaigns has become an increasingly significant phenomenon in Indonesia. Music not only acts as a means of strengthening political identity, but also as a tool for mass mobilization, political expression and the formation of public opinion. In the context of political campaigns, theme songs become symbols of the vision and values promoted by political parties, while political concerts become an opportunity to voice political aspirations and build mass support. Music is also used as a medium to express political and social views, where various musical genres such as rock, punk and hip-hop are used by musicians to voice dissatisfaction with political and social conditions in Indonesia. Song lyrics often contain political messages that reflect the views of a particular political party or social movement, helping to shape the political views and attitudes of listeners. Apart from that, music is also a tool to represent local political and cultural identities, strengthen social ties, and mobilize the masses at the regional level. However, political expression through music is also faced with challenges such as restrictions on freedom of expression and the risk of repression against musicians who are critical of the government. Therefore, it is important for governments and society to ensure that freedom of expression is respected and that musicians have space to express their political views without fear of repression. In this way, music can continue to be a positive force in political and social formation in Indonesia, helping to strengthen democracy and community involvement in the political process.